The mediating effect of MIS on warehousing HCM and efficiency in small and medium enterprises (SMEs) - Mohd Saifudin, Adam; Saud, Mohammad Basir; Bahaudin, Ahmad Yusni (Langkawi, Malaysia, 2014)
Challenges on issues and problems of warehouse efficiencies are always the major concern in the business globalization process.As part of the major logistics and supply chain management activities, warehousing is always part of the strategic and competency plan for companies in enhancing their positions in the logistics industries as their services providers.The objectives of this paper is to examine whether there is any mediating effect of warehousing Management Information System (MIS) in the relationship between warehousing Human Capital Management (HCM) and warehouse efficiency.Overall 182 Small and medium Enterprises (SMEs) were involved in this study with the findings showed that there is a strong relationship between the warehousing operations and warehouse efficiency.The findings indicate the important of warehouse efficiency in the manufacturing firms.Theoretically, the research contributes to the growth and development of the warehouse efficiency theories.Practically it would contribute the owners or warehouse managers of the manufacturing firms in making the right management decisions regarding the warehousing.Therefore, this study prov ides new knowledge and important insights of warehousing attributes that will benefit manufacturing firms and other related industries, particularly for SMEs in Malaysia.